2022
DOI: 10.1136/jitc-2021-003793
|View full text |Cite|
|
Sign up to set email alerts
|

Ccl3 enhances docetaxel chemosensitivity in breast cancer by triggering proinflammatory macrophage polarization

Abstract: BackgroundAlthough the antitumor efficacy of docetaxel (DTX) has long been attributed to the antimitotic activities, its impact on the tumor microenvironment (TME) has recently gained more attention. Macrophages are a major component of the TME and play a critical role in DTX efficacy; however, the underlying action mechanisms remain unclear.MethodsDTX chemotherapeutic efficacy was demonstrated via both macrophage depletion and C–C motif chemokine ligand 3 (Ccl3)-knockout transgenic allograft mouse model. Ccl3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…CCL20 not only facilitates the expansion of BCSCs but also enhances drug resistance in TNBC 153 . C-C Motif Chemokine Ligand 3 (CCL3) from cancer cells and macrophages enhances the phagocytic ability of docetaxel-induced M1 macrophages to BCSCs 154 . Blocking the C-X-C motif chemokine ligand-1 (CXCL1) produced by BCSCs impedes BCSC proliferation and mammosphere formation 155 .…”
Section: The Tumor Microenvironment (Tme) Regulates Bcscsmentioning
confidence: 99%
“…CCL20 not only facilitates the expansion of BCSCs but also enhances drug resistance in TNBC 153 . C-C Motif Chemokine Ligand 3 (CCL3) from cancer cells and macrophages enhances the phagocytic ability of docetaxel-induced M1 macrophages to BCSCs 154 . Blocking the C-X-C motif chemokine ligand-1 (CXCL1) produced by BCSCs impedes BCSC proliferation and mammosphere formation 155 .…”
Section: The Tumor Microenvironment (Tme) Regulates Bcscsmentioning
confidence: 99%
“… 57 , 58 Our recent reports showed that DTX induced C-C motif chemokine ligand 3 (CCL3) secretion in macrophages and triggered proinflammatory polarization of macrophages to inhibit breast cancer progression. 59 However, most patients eventually become chemo-resistant accompanied with tumor progression. There is considerable evidence that CSC enrichment played a key role in contributing to chemotherapy resistance of DTX.…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al found that docetaxel-induced Ccl3 could promote the proinflammatory macrophage polarization and subsequently accelerate phagocytosis of tumor cells. [45] In recent years, lncRNA-based prognostic signature for BRCA have been emerging. Lv et al developed an m6A-related lncRNA signature as predictive biomarkers for BRCA.…”
Section: Discussionmentioning
confidence: 99%